2017
DOI: 10.1038/s41598-017-09703-2
|View full text |Cite
|
Sign up to set email alerts
|

Large and accessible conductivity of charged domain walls in lithium niobate

Abstract: Ferroelectric domain walls are interfaces between areas of a material that exhibits different directions of spontaneous polarization. The properties of domain walls can be very different from those of the undisturbed material. Metallic-like conductivity of charged domain walls (CDWs) in nominally insulating ferroelectrics was predicted in 1973 and detected recently. This important effect is still in its infancy: The electric currents are still smaller than expected, the access to the conductivity at CDWs is ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 45 publications
(74 reference statements)
4
93
1
2
Order By: Relevance
“…38 Also, a correlation between the local concentration of charged dopants and the CDW conductance was established using the EELS TEM technique. 40 In 2017, record-breaking conductivity was reported for 180°C DWs in LiNbO 3 crystals, 6,76,99 while the earlier studies reported only transient currents 66 and d.c. conductivity under superbandgap illumination. 55 We highlight here the results from ref.…”
Section: Cdw Conductivitymentioning
confidence: 97%
See 4 more Smart Citations
“…38 Also, a correlation between the local concentration of charged dopants and the CDW conductance was established using the EELS TEM technique. 40 In 2017, record-breaking conductivity was reported for 180°C DWs in LiNbO 3 crystals, 6,76,99 while the earlier studies reported only transient currents 66 and d.c. conductivity under superbandgap illumination. 55 We highlight here the results from ref.…”
Section: Cdw Conductivitymentioning
confidence: 97%
“…Here, the total resistance extracted from the I-V characteristic can be approximated by R = F/σ S where F ≈ 0.72•log(5d/a) is a dimensionless geometric factor accounting for a sharp convergence of stream lines of the current density from continuous bottom electrode to the tip. 6 Fortunately, it depends weakly on the ratio of the sample thickness d to the tip contact length a facilitating estimates of σ S and σ from experimental data.…”
Section: Cdw Conductivitymentioning
confidence: 99%
See 3 more Smart Citations